Damage assessment of concrete beams repaired with basalt fiber-reinforced polymer sheets through digital image correlation and acoustic emission - Jianmei Chang; Yadong Yao; Ke Liu; Yonghua Wang; Meng Yan; Yi Bao (Case Studies in Construction Materials, 2024)
Basalt fiber-reinforced polymer (BFRP) has high mechanical strengths as a repairing material but exhibits low ductility. This paper investigates the damage process of reinforced concrete beams repaired using BFRP sheets, aimed at understanding the underlying mechanisms of achieving structural ductility when BFRP sheets are used. The damage process was assessed using digital image correlation (DIC) and acoustic emission (AE) techniques applied to monitor surface and internal damages of three full-scale concrete beams subjected to four-point bending. A beam was first loaded to crack, then repaired with BFRP sheets, and finally reloaded to failure. Surface strain fields and cracks were monitored using a DIC method, and cracking events were monitored using AE sensors deployed at different positions of the beams. The AE signals were analyzed to assess the damage process. The test results indicated that (1) tensile cracks predominated throughout the loading process; (2) the BFRP sheets hindered the widening of cracks and promoted the generation of fine cracks; and (3) the development of concrete cracks promoted interfacial debonding at steel-concrete and BFRP-concrete interfaces. A combination of different types of cracks and interfacial debonding helped the repaired beam achieve ductile flexural behaviors.